Discrepancies in HLA typing: use of different methods to confirm doubtful or inconclusive results - Rejane Cristina Ribas-Silva; Adriana Danmvolf Ribas; Luciana Borges Giarola; Marina Raduy Botelho; Marco Antônio Braga; Sueli Donizete Borelli (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.15575 The major histocompatibility complex (MHC) is a set of genes found on the short arm of chromosome 6. MHC molecules in human beings are known as human leukocyte antigens (HLA). HLA polymorphism can be determined by serological and molecular typing methods, which may yield discordant results. The present analysis performed HLA typing of samples with discordant results by PCR-SSP and PCR-SSO, so that typing discrepancies could be clarified. The cross-sectional study analyzed 33 samples from individuals included in an HLA-disease association study. Discrepant alleles were observed in 6 of 33 samples. Discordant samples were retyped using One Lambda Micro SSP™, Dynal RELI™ SSO and Luminex™ SSO assays for HLA class I (HLA-A, HLA-B) and class II (HLA-DRB1) molecules. The three methods produced concordant results after HLA retyping. Human error occurred in interpreting the initial results, which led to discrepancies in the results obtained. The participation of experienced professionals and the availability of at least two different methods to confirm doubtful or inconclusive results are mandatory for effective HLA typing.